Isolation and Characterization of Intestinal Epithelial Cells from Normal and SIV-Infected Rhesus Macaques - Pan, Diganta; Das, Arpita; Liu, David; Veazey, Ronald S.; Pahar, Bapi (PLOS ONE, 2012)
Impairment of intestinal epithelial barriers contributes to the progression of HIV/SIV infection and leads to generalized HIV-induced immune-cell activation during chronic infection. Rhesus macaques are the major animal model for studying HIV pathogenesis. However, detailed characterization of isolated rhesus epithelial cells (ECs) from intestinal tissues is not well defined. It is also not well documented whether isolated ECs had any other cell contaminants from intestinal tissues during the time of processing that might hamper interpretation of EC preparations or cultures. In this study, we identify and characterize ECs based on flow cytometry and immunohistochemistry methods using various enzymatic and mechanical isolation techniques to enrich ECs from intestinal tissues. This study shows that normal healthy ECs differentially express HLA-DR, CD23, CD27, CD90, CD95 and IL-10R markers. Early apoptosis and upregulation of ICAM-1 and HLA-DR in intestinal ECs are thought to be the key features in SIV mediated enteropathy. The data suggest that intestinal ECs might be playing an important role in mucosal immune responses by regulating the expression of different important regulatory and adhesion molecules and their function.